Fetus In Fetu With Myelomeningocele - Meriem Zhim MD; Khadija Laasri MD; Amine Naggar MD; Soufiane Rostoum MD; Kaoutar Sfar MD; Nazik Allali PhD; Siham El Haddad PhD; Latifa Chat PhD (Global Pediatric Health, 2023)
Fetus in fetu is an uncommon medical anomaly characterized by the presence of a malformed fetus within the body of a living twin. Although the retroperitoneum is the most typical location, occurrences in the sacrococcygeal and dorsolumbar regions are rare. Ongoing debates center around its embryopathogenesis, debating whether it is a highly specialized teratoma or a result of parasitic twinning in a monozygotic monochorionic diamniotic pregnancy. Notably, distinguishing factors such as vertebral bodies and limbs are pivotal in discerning FIF from teratomas. Diagnostic imaging techniques are integral for preoperative diagnosis, with histopathological examination confirming the condition’s presence